Developing a validated instrument to measure preservice teachers' ICT competencies: Meeting the demands of the 21st century. (23rd December 2015) - Tondeur, Jo; Aesaert, Koen; Pynoo, Bram; van Braak, Johan; Fraeyman, Norbert; Erstad, Ola
Abstract: The main objective of this study is to develop a self‐report instrument to measure preservice teachers' ICT competencies in education. The questionnaire items of this instrument are based on an existing comprehensive framework and were created with input from experts in the field. The data were collected from a sample of 931 final‐year preservice teachers in Flanders (Belgium). A first subsample was used for an exploratory factor analysis, and a second one to verify the identified factor structure via confirmatory factor analysis. A two‐factor structure of ICT competencies was identified: (1) competencies to support pupils for ICT use in class and (2) competencies to use ICT for instructional design. This two‐factor structure was confirmed in the confirmatory factor analysis. Recommendations are made on how this reliable instrument can help assess the level and progress of preservice teachers' ICT competencies.